Regulation of P450 oxidoreductase by gonadotropins in rat ovary and its effect on estrogen production - Inaoka, Yoshihiko; Yazawa, Takashi; Mizutani, Tetsuya; Kokame, Koichi; Kangawa, Kenji; Uesaka, Miki; Umezawa, Akihiro; Miyamoto, Kaoru (Reproductive biology and endocrinology, 2008)
P450 oxidoreductase (POR) catalyzes electron transfer to microsomal P450 enzymes. Its deficiency causes Antley-Bixler syndrome (ABS), and about half the patients with ABS have ambiguous genitalia and/or impaired steroidogenesis. POR mRNA expression is up-regulated when mesenchymal stem cells (MSCs) differentiate into steroidogenic cells, suggesting that the regulation of POR gene expression is important for steroidogenesis. In this context we examined the regulation of POR expression in ovarian granulosa cells by gonadotropins, and its possible role in steroidogenesis. Changes in gene expression in MSCs during differentiation into steroidogenic cells were examined by DNA microarray analysis. Changes in mRNA and protein expression of POR in the rat ovary or in granulosa cells induced by gonadotropin treatment were examined by reverse transcription-polymerase chain reaction and western blotting. Effects of transient expression of wild-type or mutant (R457H or V492E) POR proteins on the production of estrone in COS-7 cells were examined in vitro. Effects of POR knockdown were also examined in estrogen producing cell-line, KGN cells. POR mRNA was induced in MSCs following transduction with the SF-1 retrovirus, and was further increased by cAMP treatment. Expression of POR mRNA, as well as Cyp19 mRNA, in the rat ovary were induced by equine chorionic gonadotropin and human chorionic gonadotropin. POR mRNA and protein were also induced by follicle stimulating hormone in primary cultured rat granulosa cells, and the induction pattern was similar to that for aromatase. Transient expression of POR in COS-7 cells, which expressed a constant amount of aromatase protein, greatly increased the rate of conversion of androstenedione to estrone, in a dose-dependent manner. The expression of mutant POR proteins (R457H or V492E), such as those found in ABS patients, had much less effect on aromatase activity than expression of wild-type POR proteins. Knockdown of endogenous POR protein in KGN human granulosa cells led to reduced estrone production, indicating that endogenous POR affected aromatase activity. We demonstrated that the expression of POR, together with that of aromatase, was regulated by gonadotropins, and that its induction could up-regulate aromatase activity in the ovary, resulting in a coordinated increase in estrogen production.